MEMPELAJARI PERAN SOSIAL WANITA DALAM OLAHRAGA DENGAN KONTROVERSI CITRA PATRIARKI DIMASYARAKAT - zani, yulia; Eri Barlian; Padli (Pendidikan Kepelatihan Olahraga FKIP Universitas Riau, 2023)
Women are known as people who have to obey men so that the stigma in women's society as people who have to stay at home and take responsibility in it, in accordance with the existing stigma, people are starting to know sports and women have managed to get gold as proof that women are not weak. With his character, women in sports are not as thought. Until now, women have been considered to complement the zuforia of competitions, such as cheering and cheerleading, but so far many women have been able to show achievements. This research aims to find out the social role of women in sports with the patriarchal image controversy. The method used in this research is descriptive qualitative using observation, interviews and literacy. Based on the results and discussion through women's sports, character in sports can be formed, as well as the values ​​of cooperation, sportsmanship, honesty, responsibility. The conclusion in this research is that women are indispensable in sport by adopting an attitude of responsibility, fairness and sportsmanship. Keyword: sosial role of women, patriarchal image, sport